Immigration, Housing Rents, and Residential Segregation: Evidence from Syrian Refugees in Turkey - Binnur Balkan; Elif Ozcan Tok; Huzeyfe Torun; Semih Tumen (Institute of Labor Economics (IZA), 2018)
The massive inflow of Syrian refugees is argued to drastically affect various social and economic outcomes in the hosting countries and regions. In this paper, we use micro-level data to investigate whether the Syrian refugee inflows have affected the market for housing rentals in Turkey. The unexpected arrival of a large number of refugees due to civil conflict in Syria is used to construct a quasi-experimental design. Since the construction of new housing units takes a long time, refugee inflow resembles a positive demand shock to the sector. We find that the refugee inflows have led to an increase in the rents of higher-quality housing units, while there is no statistically significant effect in the rents of lower-quality units. This finding supports a residential segregation story, which suggests that the refugee wave has increased the demand for native-dominant neighborhoods with better amenities especially among natives. We argue that negative attitudes towards refugees – potentially due to refugee-native conflict along several dimensions – may be generating this result.
Keywords: C21; F22; R21; R23; 330; Syrian refugees; immigration; housing rents; quasi-experimental design; Turkey